The impact of contraceptive counseling on choice of method after voluntary termination of pregnancy: systematic review - Palma,Sara (2022)
Abstract Introduction: The voluntary termination of pregnancy (VTP), is a public health problem that reveals absence, discontinuity or incorrect use of the contraceptive. Scientific evidence suggests that the ideal time to adhere to a contraceptive is during VTP, since women do not wish to live the same experience. Objective: To know the impact of contraceptive counseling (CC) on the choice of a method by women to experience VTP. Methods: Literature review according to the guidelines of the Joanna Briggs Institute, carried out from January 1st to 31st, repeated from October 2nd to 5th, 2020, with the research question “What is the impact of contraceptive counseling given to women in the process of VTP, in choosing the method?”. The EBSCO platform and the CINAHL, MedicLatina and Cochrane Central Register of Controlled Trials databases were used. Results: Eleven were eligible, published in English between 2014 and 2020 in different clinical contexts. Evidence shows that: it is after VTP that most women choose a contraceptive and adherence is related to the quality of the information transmitted; the CC must respond to the needs of women undergoing VTP; to provide quality CC it is essential to train professionals. Conclusion: Quality CC as an integral part of the VTP process, combined with the accessibility and free use of contraceptives, favors the choice and adherence to contraceptives.